Cyberbullying among secondary school teachers by parents - Rüyam Küçüksüleymanoğlu (International Journal of Evaluation and Research in Education (IJERE), 2019)
Cyberbullying which is known as violence on the Internet is a dimension of peer bullying takes places through electronic communication technologies. Cyberbullying which can occur in any environment regardless of the time and place is the way in which individuals with higher ability to use communication technologies to lead other individuals in a series of negative behaviors over time. With the rapid development of technology and the ease with which internet access becomes easier and cheaper, it becomes a problem that needs to be studied more and more importantly day by day. Facebook, twitter and whatss up, the most widely used social network today, has the potential to become the most commonplace for cyberbullying behaviors. The purpose of this study was to determine cyberbullying towards teachers by parents in secondary schools based on teachers views according to sex, tenure and school size. The sample of the study was 181 teachers from 14 secondary schools. The experiences and perspectives of 181 teachers were assessed regarding the incidence and perceptions of the likelihood of cyber harassment by parents. The results presented here indicate that nearly3/4 of teachers in the sample had received harassing or threatening messages from parents.